Health Belief Model–Based Education on Post-Stroke Neurological Disorders Affecting Oral Health: A Quasi-Experimental Study - Jenal Abidin; Sepriana Urianti (Jurnal Ilmiah Kesehatan (JIKA), 2026)
Stroke is no longer limited to the elderly but is increasingly found among younger populations. However, adolescents’ knowledge and attitudes toward stroke remain low. Stroke can affect oral and facial tissues, disrupting essential daily functions such as eating, drinking, swallowing, and communication. This study aimed to examine the effect of Health Belief Model (HBM)–based health education on students’ knowledge and attitudes regarding post-stroke neurological disorders affecting oral health. The study employed a quasi-experimental approach using a non-equivalent control group design among 64 first-year students of Dental Technology and Dental Health at Tanjung Karang Polytechnic. Participants were chosen through simple random sampling and then assigned to experimental and control groups. The study consisted of three stages: pre-test, intervention, and post-test. Knowledge was measured using 20 multiple-choice questions, while attitudes were assessed using 15 Likert-scale statements. Data were analysed using Paired t-test, Wilcoxon signed-rank, Independent t-test, and Mann-Whitney with SPSS version 26. The results showed significant improvements in both groups (p < 0.05), with greater gains in the experimental group for knowledge (t = 24.334 vs. 8.184) and attitudes (t = 13.538 vs. Z = -4.944). However, based on the Independent t-test and Mann-Whitney test, the experimental group showed significantly greater improvements than the control group (p < 0.05). HBM-based health education was more effective than conventional education in improving students’ knowledge and attitudes regarding post-stroke neurological disorders affecting oral health. The HBM approach was recommended as an effective educational framework for health promotion in post-stroke oral health care.